Epiphytic Orchid Inventory and The Host In Bantarbolang Nature Reserve - Central Java - Rahmi Mutia Mawardi; Wiwik Herawati; Pudji Widodo (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Bantarbolang Nature Reserve is located in the northern part of Central Java Province. The study aiming to verify the plant species of epiphytic orchids and the host tree in the area of Bantarbolang Nature Reserve was conducted in February to April 2019. The research method used in the research was explorative methods. Data were analyzed descriptively. It was recorded that there were 5 epiphytic orchid species, i.e. Rhynchostylis retusa, Aerides odorata, Cymbidium bicolor, Dendrobium crumenatum and Ascocentrum miniatum. The number of orchids found was 148 individuals, the most common species was Rhynchostylis retusa. The host trees are teak (Tectona grandis), putat (Barringtonia acutangula), bulu (Ficus annulata) and bungur (Lagerstroemia speciosa) with characteristics of hard stems, cracked surface texture, rough, mossy and not easy to peel.